Surnames with Multifunctional Suffixes in the Anthroponymycon of Lutsk (Linguostylistic Studies, 2016)
The article analyzes surnames with multifunctional suffixes -kо, -ай, -ей, -ій, which are characterized by quite low productivity. The emphasis is laid on the homonymous and appellative lexicon reflected in the stems of these names and on the peculiarities of their derivation. The author considers surnames, derived from the old Slavic or Christian names (e.g Gun'ko, Ievtushko, Lavrii, Kubai, Romai) mainly as names of double word-building motivation. It has been revealed that the surnames motivated by appellatives with an initial meaning of diminutiveness (Kolin’ko, Cherevko), attributiveness (Bagrii, Kuchmei, Labai), subjective evaluation (Halai, Ostrii, Kyrdei) or those indicating to profession (Shablii, Skrypai) have been created in lexico-semantic way. In family names of morphological-structure type the formants under the analysis of the article perform patronymic function. Key words: surname, anthroponym, appellative, personal name, old Slavic name, Christian name, suffix. References